Letrozole plus metformin versus letrozole alone in the treatment of symptomatic endometrioma - Saha, Chandana; Anwary, Shaheen Ara; Sultana, Rebeka; Rolly, Suraiya Jahan; Tarique, Mostafa M. Al; Mahmud, Shihan; Salam, Sharmin; Rani, Reeta; Banu, Jesmine (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Endometriosis is a chronic, estrogen-dependent inflammatory disorder affecting up to 10% of reproductive-age women, with endometrioma present in 17-44% of cases and linked to pain and subfertility. This study aims to compare the efficacy of letrozole plus metformin versus letrozole alone in the treatment of women with symptomatic endometrioma. The aim of the study was to evaluate the efficacy of letrozole plus metformin versus letrozole alone in reducing endometrioma size, pain, and serum IL-6 levels, with comparable side effects. Methods: This randomized controlled trial (RCT) was conducted at the department of reproductive endocrinology and infertility, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka (January 2022 to June 2023). Fifty women with endometrioma (<5 cm) received either letrozole (2.5 mg/day) plus metformin (1500 mg/day) or letrozole alone for 12 weeks. Outcomes (endometrioma size, visual analog scale (VAS) pain score, IL-6 levels) were analyzed using SPSSv23 (paired/unpaired t tests; p<0.05 significant). Results: Letrozole plus metformin (Group A) and letrozole alone (Group B) were compared in 50 women with endometrioma, with no significant baseline differences (p>0.05). After 3 months, group A showed greater reduction in endometrioma size (p=0.003), pain scores, and IL-6 levels, though the latter two were not statistically different between groups (p>0.05). Side effects were mild and similar in both groups, indicating improved efficacy of the combination therapy with comparable safety. Conclusions: Combined letrozole and metformin therapy significantly reduces endometrioma size, pain, and IL-6 levels more than letrozole alone, offering a promising treatment for endometriosis patients seeking fertility.